(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the ways of developing creativity and thinking of future music teachers through artpedagogy, which is a modern form of education recognized as a part of the field of pedagogy. It is also supposed to describe the methodological approaches to the formation of the professional readiness of students with a high level of knowledge in the field of art to see the systematized results of creative activity.